Membrane‐acting biomimetic peptoids against visceral leishmaniasis. Issue 3 (7th February 2023) - Kumar, Vivek; Lin, Jennifer S.; Molchanova, Natalia; Fortkort, John A.; Reckmann, Carolin; Bräse, Stefan; Jenssen, Håvard; Barron, Annelise E.; Chugh, Archana
Abstract : Visceral leishmaniasis (VL) is among the most neglected tropical diseases in the world. Drug cell permeability is essential for killing the intracellular residing parasites responsible for VL, making cell‐permeating peptides a logical choice to address VL. Unfortunately, the limited biological stability of peptides restricts their usage. Sequence‐specific oligo‐ N ‐substituted glycines ('peptoids') are a class of peptide mimics that offers an excellent alternative to peptides in terms of ease of synthesis and good biostability. We tested peptoids against the parasite Leishmania donovani in both forms, that is, intracellular amastigotes and promastigotes. N ‐alkyl hydrophobic chain addition (lipidation) and bromination of oligopeptoids yielded compounds with good antileishmanial activity against both forms, showing the promise of these antiparasitic peptoids as potential drug candidates to treat VL. Abstract : Biomimetic peptoids have membrane rupturing activity on VL, causing species L. donovani inhibition within 4 h of treatment. Hydrophobic lipid tail attachment further aids in membrane attachment and thereby improves activity against both promastigote and intracellular amastigote forms.